Plasmodium falciparum PfEMP1 modulates monocyte/macrophage transcription factor activation, and cytokine and chemokine responses - Sampaio, N; Eriksson, E; Schofield, L (American Society for Microbiology, 2017)
Immunity to Plasmodium falciparum malaria is slow to develop, and it is often asserted that malaria suppresses host immunity, although this is poorly understood and the molecular basis for such activity remains unknown. P. falciparum Erythrocyte Membrane Protein 1 (PfEMP1) is a virulence factor that plays a key role in parasite-host interactions. We investigated the immunosuppressive effect of PfEMP1 on monocytes/macrophages, which are central to the anti-parasitic innate response. RAW macrophages and human primary monocytes were stimulated with wild-type 3D7 or CS2 parasites or transgenic PfEMP1-null parasites. To study the immunomodulatory effect of PfEMP1, transcription factor activation and cytokine and chemokine responses were measured. Activation of NF-κB was significantly lower in macrophages stimulated with parasites that express PfEMP1 at the red blood cell surface-membrane compared to PfEMP1-null parasites. Modulation of additional transcription factors, including CREB, also occurred, resulting in reduced immune gene expression and decreased TNF and IL-10 release. Similarly, human monocytes released less IL-1β, IL-6, IL-10, MCP-1, MIP-1α, MIP-1β and TNF specifically in response to VAR2CSA PfEMP1-containing parasites compared to PfEMP1-null parasites, suggesting this immune regulation by PfEMP1 is important in naturally occurring infections. These results indicate that PfEMP1 is an immune-modulatory molecule that affects the activation of a range of transcription factors, dampening cytokine and chemokine responses. Therefore, these findings describe a potential molecular basis for immune suppression by P. falciparum.